Cardiovascular Diseases and Schizophrenia in India: Evidence, Gaps, and Way Forward - Padmavati, Ramachandran; Kantipudi, Suvarna Jyothi; Balasubramanian, Suhavana; Raghavan, Vijaya (Frontiers in Psychiatry, 2021)
Background: The importance of physical health among persons with schizophrenia is well-established. Studies from developed and developing countries indicated a strong association between cardiovascular diseases and schizophrenia, while evidence from India is scattered and in its infancy. Hence, the aims of the study were to collate available studies from India on cardiovascular diseases among persons with schizophrenia, identify knowledge gaps and challenges, and discuss recommendations to improve clinical care and research on cardiovascular diseases among persons with schizophrenia in India. Materials and methods: A comprehensive literature review of Indian studies on cardiovascular diseases and schizophrenia was conducted to collate and synthesise available knowledge. Results: Several risk factors for cardiovascular disease predominated among persons with schizophrenia. Metabolic syndrome and obesity were the key factors that were reported. Knowledge gaps were identified with respect to the prevalence of cardiovascular diseases among persons with schizophrenia. Sparse research in interventions to prevent and reduce the impact of cardiovascular diseases among persons with schizophrenia was noted. Conclusion: Targeted efforts are needed at the clinic, community, and policy levels to understand the impact of cardiovascular diseases among persons with schizophrenia. Robust and feasible interventions targeting cardiovascular diseases and its varied risk factors in persons with schizophrenia, that can be implemented in tertiary mental health services, need to be developed and tested.